Factores biosocioculturales y nivel de información de madres primíparas sobre el cuidado del recién nacido. Trujillo, 2016 - Escobedo Martínez, Patricia Del Pilar (2016)
This research, descriptive correlational was held at the Regional Hospital of Trujillo, during the month of January - February 2016, in order to establish the relationship between the biosocioculturales factors: age, level of education, marital union and occupation and the level of information of first-time mothers on newborn care. The sample consisted of 161 first-time mothers who met the inclusion criteria. For data collection instruments "Facts maternal identification information" and "scale for measuring the level of information on newborn care" were used; the information obtained was processed and analyzed by 2. test. The results are presented in tables of single and double entry. After the analysis was reached the following conclusion: the highest percentage of gilts are between 18 to 29 years 11 months and 29 days, have high school degree, are a couple, their occupation is in the home and have a level of information means about the care of the newborn; statistical significance between the variables biosocioculturales factors and level of information of first-time mothers on newborn care was found; except in the occupation factor.